A hospital study of community acquired pneumonia in the elderly. Issue 4 (April 1990) - Venkatesan, P; Gladman, J; Macfarlane, J T; Barer, D; Berman, P; Kinnear, W; Finch, R G
Abstract : Studies on community acquired pneumonia in the United States in patients over the age of 65 years have shown that Gram negative bacilli account for an appreciable proportion of cases, in addition to usual pathogens such as Streptococcus pneumoniae and Haemophilus influenzae. There have been no reports of community acquired pneumonia in the elderly in the United Kingdom. We undertook such a study to determine the clinical features, aetiology, and outcome. Seventy three patients (38 men) with ages ranging from 65 to 97 (median 79) years were studied prospectively. Pneumonia was defined as an acute lower respiratory tract infection with new, previously unrecorded shadowing on a chest radiograph. Patients with severe chronic illness in whom pneumonia was an expected terminal event were excluded. Nearly all the patients (96%) had respiratory symptoms or signs but many had features that might obscure the true diagnosis of pneumonia. Over half the patients had non-respiratory symptoms and over a third had no systemic signs of infection. A pathogen was identified in 43% of patients, most commonly Streptococcus pneumoniae, Haemophilus influenzae and influenza B virus. Gram negative bacilli were not seen. The mortality rate was high (33%). Early deaths were due to infection whereas later deaths were associated with other factors, such as stroke (two patients) and pulmonary embolism (two patients). Prognostic indicators for mortality were apyrexia, systolic hypotension, increasing hypoxaemia, and new urinary incontinence. As the range of pathogens causing pneumonia was the same in the elderly in this study as in other age groups it is suggested that initial antibiotic treatment for patients in this age group should always cover S pneumoniae and H influenzae.